Urban art: Creating the urban with art: proceedings of the International Conference at Humboldt-Universität zu Berlin, 15-16 July, 2016 - Blanché, Ulrich; Hoppe, Ilaria (Pedro Soares Neves, 2018)
Urban Art: Creating the Urban with Art Proceedings of the International Conference at Humboldt-Universität zu Berlin, 15-16 July, 2016 Published July 2018 - ISBN: 978-989-97712-8-4 Urban Art....
Gesehen am 21.08.2018
Keywords: Konferenzschrift -- 15.07.2016-16.07.2016 -- Berlin